Analisis Persepsi Masyarakat Terhadap Aktivitas Media Sosial dalam Pembentukan Opini Publik di Era Digital - Zahy Alwaan, Alfathi; Barqy Muhammad, Agil; Sri Wahyuni, Intan; Hidayah, Wardatul (Pimpinan Cabang Muhammadiyah Kramat Jati, 2025)
The digital era has changed the landscape of communication and social interaction, where social media plays a central role in shaping public opinion. This study aims to analyze public perceptions of social media activities in shaping public opinion. Using a qualitative approach with a phenomenological study method, data were collected through in-depth interviews with various community groups active in social media. The results of the study indicate that social media functions as a dynamic discussion space, allowing active participation of the community in social, political, and cultural issues. However, there are differences in the pattern of receiving and interpreting information, which is influenced by factors such as the level of digital literacy, trust in information sources, and social media algorithms. In addition, it was found that opinion polarization often occurs due to cognitive bias and the echo chamber effect that strengthens certain points of view. This study highlights the importance of digital literacy education to increase public awareness in filtering information and avoiding disinformation. These findings are expected to provide insight for academics, policy makers, and media practitioners in managing the impact of social media on public opinion in the digital era.